2021
DOI: 10.3390/diagnostics11050860
|View full text |Cite
|
Sign up to set email alerts
|

Serum and Urine Biomarker Leucine-Rich Alpha-2 Glycoprotein 1 Differentiates Pediatric Acute Complicated and Uncomplicated Appendicitis

Abstract: Purpose: This prospective, single-center cohort study analyzes the potential of inflammatory protein mediator leucine-rich alpha-2 glycoprotein 1 (LRG1) for the early and accurate diagnosis of acute appendicitis (AA), and differentiation of acute complicated (AcA) from uncomplicated appendicitis (AuA). Methods: Participants were divided into the AcA, AuA, and control groups, and their serum (s-LRG1) and urine LRG1 (u-LRG1) levels were assayed preoperatively on the second and fifth postoperative days. Results: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
38
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(39 citation statements)
references
References 33 publications
0
38
0
1
Order By: Relevance
“…Furthermore, due to the restrictions on the number of participants admitted to this study, the control group consisted of the patients with different surgical conditions, such as fractures, testicular torsion, etc. and the patients with non-specific abdominal pain were not included [ 43 ]. On the contrary, to differentiate acute appendicitis from non-specific abdominal pain, in our control group, we included children who had non-specific abdominal pain but in whom the diagnosis of acute appendicitis had been ruled out by diagnostic procedures.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, due to the restrictions on the number of participants admitted to this study, the control group consisted of the patients with different surgical conditions, such as fractures, testicular torsion, etc. and the patients with non-specific abdominal pain were not included [ 43 ]. On the contrary, to differentiate acute appendicitis from non-specific abdominal pain, in our control group, we included children who had non-specific abdominal pain but in whom the diagnosis of acute appendicitis had been ruled out by diagnostic procedures.…”
Section: Discussionmentioning
confidence: 99%
“…However, extensive use of diagnostic imaging has been severely restricted by a variety of factors, including immediate accessibility, cost, exposure of children to radiation from CT scans and the national guidelines [ 35 , 36 ]. Notable studies are focused on utilizing new biomarkers of inflammation that are accessible, easily detected and affordable in order to accurately diagnose acute appendicitis [ 1 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Acute uncomplicated appendicitis may be treated solely with antibiotics; however, when it progresses to acute complicated appendicitis, surgical treatment is necessary. Delayed diagnosis and treatment of acute appendicitis may lead to complications such as peritonitis, intra-abdominal abscess, sepsis, ileus, or even patient death [ 16 ]. The COVID-19 pandemic gave rise to many fears about hospitalisation and prolonged stays in the ED, considering potential cross-infection and delays in treatment due to disease control measures and other logistical restrictions.…”
Section: Discussionmentioning
confidence: 99%
“…Increased pro-inflammatory cytokines, especially IL-6, has been shown to indirectly increase LRG. [19][20][21] Studies assessing LRG levels in the synovial fluid of RA and SpA patients have previously been conducted, with varying results being obtained. Several studies examining LRG levels in synovial fluid, including one by Birkelund et al, reported that synovial fluid proteomics analysis from SpA and RA patients showed striking differences in the amount of innate immune system proteins, especially those from neutrophil granulocytes, including LRG.…”
Section: Introductionmentioning
confidence: 99%